Development of a Community-Based Intervention Model through Infused Water Consumption for Blood Pressure Control in Hypertensive Patients - Lisnawati, Ica; Anwari, Muhammad; Munadi, M. Hasni; Panda, M. Imannuddin; hair, Abdul; Prananda, Yuda; Ratnatina, Ratnatina; Ermayanty, Wafa; Ra’fah, Siti; Faujiah, Utami (OMNICODE Journal (Omnicompetence Community Developement Journal), 2024)
Hypertension is a non-communicable disease that is commonly suffered by the people in Hulu Sungai Utara Regency. Based on a windshield survey conducted in RT.2 of Kalumpang Luar Village, it was found that around 39.6% of the population suffers from hypertension. This disease is often referred to as a "silent killer" because many hypertension cases do not show clear symptoms, yet it can lead to serious complications such as stroke, heart attack, kidney failure, and other organ damage if not properly controlled. Problem Solving for Better Health activities have been carried out, including education, blood pressure screening, and complementary therapy through the administration of infused water. Infused water contains potassium, which helps balance sodium in the body by removing excess sodium through urine and relaxing the walls of blood vessels to lower blood pressure. The Problem Solving for Better Health program implemented in RT. 2 of Kalumpang Luar Village successfully increased the community’s knowledge and skills in preparing and consuming infused water as a complementary therapy for people with hypertension.